Dietary polyphenols and metabolic syndrome among Iranian adults - Sohrab, Golbon; Hosseinpour-Niazi, Somayeh; Hejazi, Jalal; Yuzbashian, Emad; Mirmiran, Parvin; Azizi, Fereidoun (International journal of food sciences and nutrition, 2013)
Abstract Aim: The aim of this study was to investigate the association between total polyphenol intake, its subclasses (including flavonoids, phenolic acids, stilbenes and lignans), and the metabolic syndrome (MetS). Methods: This population-based cross-sectional study was conducted on a representative of 2618 adults, aged 19 to 84 years. Dietary intake was assessed using a validated food-frequency questionnaire and intakes of total polyphenol and four main subclasses of polyphenol including flavonoids, phenolic acids, stilbenes and lignans were determined. Results: Higher consumption of flavonoid intakes was associated with lower odds of enlarged waist circumference, hypertriglyceridemia, low HDL cholesterol, hyperglycemia, hypertension and MetS. Subjects in the highest quartile of lignan intakes had higher odds of having hypertriglyceridemia and hyperglycemia. Subjects in the highest quartile of stilbene intakes had higher odds of having hypertension. Conclusion: Intakes of selected subclasses of polyphenol such as flavonoids are associated with a lower prevalence of MetS among Tehranians.